Impact on Employees’ Productivity On-shift in Workplace Environment During Pandemic - Mullanda Poovaiah, Shivani; Mathew, Alphy (Ushus Journal of Business Management, 2022)
The workplace environment plays an important role in employees' desire for work and outcome. Work and workplace have significant relation, when workers have emotion towards their job, their productivity increases and employees should have a definite environment to work in so that absenteeism will subsidize flexibility in the workplace. An organisation's productivity and success depend on employees’ efficiency and commitment to an organization. Employee coherence will increase contribution and productivity to achieve the organization's objective. Technology has made mankind connect people through the internet from any part of the world. Likewise, employees can work from remote areas and communicate with their colleagues.